SCIENCE OF MATERIALS AND TECHNOLOGICAL ASPECTS OF PRODUCTION OF HEAT-TREATABLE LAYERS OF DIFFUSED-ALLOYED W IRE - V. G. Dashkevich (Литьë и металлургия)
Principles of a choice of modes of thermal processing of a detail with a coating are considered. As a way of reception hardfasing an alloy, it is offered diffusionaly alloying a carbonaceous wire. The way allows to adjust the content of alloying elements for achievement through hardenability a layer.